Perancangan Keselamatan dan Kesehatan Kerja pada PT. Injaplast - To, Agnes; Panjaitan, Togar W.S (Jurnal Titra, 2015)
Abstract: PT Injaplast is a manufacturing company that produces a plastic sacks (plastic woven bags,) which is located in Jl. Margomulyo No. 35, Surabaya. PT Injaplast currently doesnât have a Occupational Safety and Health, so that the work accident still quite high. It can be seen from the companyâs work accident data, which in 2013 and 2014 there are 12 minor accidents and 3 major accidents that occurred. The high rate of work accident can be minimized through the preparation of hazard identification, risk assessment, and risk control document (HIRARC). HIRARC can support the successful implemetation of K3. The purpose of HIRARC is to detect hazard exist, risk assessment, and making control to minimize the potential risk. The results of HIRARC document preparation shows that there are still many activities that endagers worker. There are 43% activities are classified as moderate risk and 15% as high risk. That risk level must be solved by making a risk control. The suggestion on risk control are giving a personal protective equipment, give safety sign (administrative control), add equipment (engineering control), and replace a personal protective equipment and tools (substitution). The estimation of decreased risk rating possibility that expected later will be created based on risk controls that have been given. The estimation of decreased risk rating possibility when the controlling risk executed is the risk with moderate category which originally was 43% decrease to 11% while the high category are initially 15% decrease to 3%.